'Mankind owes to the child the best that it has to give': prison conditions and the health situation and rights of children incarcerated with their mothers in sub-Saharan African prisons - Marie-Claire Van Hout; Rosemary Mhlanga-Gunda (BMC, 2019)
Abstract Background In recent times, sub-Saharan African (SSA) prisons have seen a substantial increase in women prisoners, including those incarcerated with children. Methods A scoping review mapped what is currently known about the health situation and unique rights violations of children incarcerated with their mothers in SSA prisons. A systematic search collected and reviewed all available and relevant published and grey literature (2000-2018). Following application of exclusion measures, 64 records remained, which represented 27 of the 49 SSA countries. These records were charted and thematically analysed. Results Four main themes were generated as follows: 1) the prison physical environment; 2) food availability, adequacy and quality; 3) provision of basic necessities and 4) availability and accessibility of health services for incarcerated children. Conclusions The review highlights the grave situation of children incarcerated with their mothers in SSA prisons, underpinned by the lack of basic necessities, inadequate hygiene, sanitation and safe drinking water, exposure to diseases in overcrowded cells, inadequate nutrition, lack of provision of clothing and bedding, and difficulties accessing paediatric care. Reported paediatric morbidity and mortality associated with such prison conditions is deeply concerning and contrary to international mandates for the rights of the child, right to health and standards of care.